eIF3a Regulates Colorectal Cancer Metastasis via Translational Activation of RhoA and Cdc42 - Mei, Chao; Liu, Chong; Gao, Ying; Dai, Wen-Ting; Zhang, Wei; Li, Xi; Liu, Zhao-Qian (Frontiers in Cell and Developmental Biology, 2022)
Tumor metastasis is the major cause of tumor relapse and cancer-associated fatality in colorectal cancer, leading to poor treatment response and reduced survival. eIF3a has been previously described as an oncogene. However, its role in colorectal cancer progression and metastasis has not been fully investigated yet. In this study, we investigated the clinical significance of eIF3a in colorectal cancer samples, including the specificity of expression as well as the predictive ability for tumor metastasis and overall survival. Mechanically, the knockdown of eIF3a obviously inhibited the proliferation and motility of malignant cells in vitro and in vivo, indicating a tumor-promoting role in disease progress. This was potentially due to the translational activation of Cdc42 and RhoA, by affecting pseudopodia formation and actin cytoskeleton remodeling. Taken together, eIF3a plays an oncogene role in colorectal cancer and accelerates the acquisition of migratory phenotype of cancer cells by translationally activating Cdc42 and RhoA. Our study identified eIF3a as a promising target for inhibiting colorectal cancer metastasis.